2000
DOI: 10.1097/00005537-200003001-00001
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Surgery for Patients With Recurrent Squamous Cell Carcinoma of the Upper Aerodigestive Tract: When Do the Ends Justify the Means?

Abstract: Objectives/Hypotheses: Salvage surgery is widely viewed as a "double-edged sword." It is the best option for many patients with recurrent cancer of the upper aerodigestive tract, especially when original therapy included irradiation, yet it may provide only modest benefit at high personal cost to the patient. The stakes are high because alternatives are of limited value. The primary objective of this study was to fully assess the value of salvage surgical procedures in the treatment oflocal and regional recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

24
510
5
30

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 545 publications
(579 citation statements)
references
References 55 publications
24
510
5
30
Order By: Relevance
“…Despite advances in various treatment modalities, the overall prognosis of HNSCC patients has not improved significantly within the last several decades. About 50 % of patients survive their disease [3]. Advanced tumors have a recurrence rate of around 20-30 % at the primary tumor site and 10-15 % in the neck [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite advances in various treatment modalities, the overall prognosis of HNSCC patients has not improved significantly within the last several decades. About 50 % of patients survive their disease [3]. Advanced tumors have a recurrence rate of around 20-30 % at the primary tumor site and 10-15 % in the neck [3].…”
Section: Introductionmentioning
confidence: 99%
“…About 50 % of patients survive their disease [3]. Advanced tumors have a recurrence rate of around 20-30 % at the primary tumor site and 10-15 % in the neck [3].…”
Section: Introductionmentioning
confidence: 99%
“…Deve ser considerada mesmo naqueles casos em que o paciente não foi submetido às terapêuticas disponíveis no primeiro tratamento 11 . Segundo Cooney et al, 12 observaram bons resultados do resgate cirúrgico em somente 5% em cinco anos, com sobrevida média livre de doença de seis meses.…”
Section: Introductionunclassified
“…Surgical removal of gross tumor mass before rRT circumvents this problem [9]. Finally, a meta-analysis of 32 surgical studies with 1,080 patients demonstrated a survival rate of 39 % at 5 years in patients treated by salvage surgery, compared with a 20-30 % overall survival rate at 2 years after rRT alone [3,10].…”
mentioning
confidence: 99%